First report of Tetracona (Agrotera) amathealis (Walker, 1859) on a Eucalyptus grandis W. Hill × Eucalyptus pellita F. Muell. (Myrtaceae) hybrid in Indonesia (Lepidoptera: Crambidae, Spilomelinae) - T. Melia; N. G. H. B. Simulingga; M. V. Maretha; R. Wijaya; R. R. Efendi; L. S. S. Oliveira; S. K. Khadan; W. de S. Tavares; M. Tarigan; A. Duran (SHILAP, 2021)
Tetracona amathealis (Walker, 1859) (Lepidoptera: Crambidae) is previously known from Australia and New Guinea, where it feeds on the native Eucalyptus tereticornis Sm. (Myrtaceae). The objective of this study was the report, for the first time, T. amathealis in Indonesia as well as to record new host plants for this insect. Were collected manually from a Eucalyptus grandis W. Hill. × Eucalyptus pellita F. Muell. hybrid commercial plantation in Riau, Sumatra, Indonesia and a sample sent for identification via molecular analysis. Our findings revealed that the molecular approach used (through sequencing of its mt-COI gene) successfully allowed the identification of the species as T. amathealis. This insect is recorded for the first time in Indonesia on a new host, a E. grandis × E. pellita hybrid.